The Relationship Between Organizational Commitment and Environmental Leadership with Community Satisfaction for Sustainable Ecotourism Development at Danau Sipin, Jambi - Citra Sherly Gita; HM Ahman Sya; Ananto Kusuma Seta; Eliana Sari; Dwi Atmanto (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The development of sustainable ecotourism requires a balanced integration of economic benefits, social well-being, and environmental conservation, with local communities playing a central role in tourism management. This study aims to examine the influence of organizational commitment and environmental leadership on community satisfaction in supporting sustainable ecotourism development at Danau Sipin, Jambi City. A quantitative, correlational research design was employed. Data were collected through questionnaires and interviews with 60 respondents, including local community members, tourism awareness groups, and stakeholders directly engaged in ecotourism management. The sampling technique combined multistage purposive sampling and simple random sampling. Data analysis included validity and reliability testing, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing using t-tests and F-tests. The results indicate that all research instruments were valid and reliable. Simultaneously, organizational commitment and environmental leadership had a significant effect on community satisfaction in sustainable ecotourism development. Partially, each independent variable also demonstrated a positive and significant influence on community satisfaction. These findings highlight the importance of strengthening organizational commitment and environmentally oriented leadership to enhance community satisfaction and participation, thereby supporting the long-term sustainability of ecotourism management at Danau Sipin, Jambi City.